Academic wrestlers' age-specific technical and tactical progress control - Bavykin, E. A.; Zinoviev, N. A.; Sidorenko, S. A. (Theory and Practice of Physical Culture, 2018)
The study makes a comparative analysis of the competitive performance profiles of the junior wrestlers who competed in the 2017 World Freestyle Wrestling Championship. The study data and analysis made it possible to profile the individual competitive performances of the junior wrestlers versus their age-specific competitive technical and tactical progress data. The wrestlers` competitive technical and tactical actions (TTA) were rated using the following rating criteria: scoring TTA; points scored; points lost; scoring attacking TTA; scoring counterattacking TTA; scoring opponent`s attacks; countered attacks; and scoring attacks intervals (SAI).